Evolution of tick vaccinology - José de la Fuente; Srikant Ghosh; Ala Tabor (Parasitology)
Ticks represent a major concern for society worldwide. Ticks are also difficult to control, and vaccines represent the most efficacious, safe, economically feasible and environmentally sustainable intervention. The evolution of tick vaccinology has been driven by multiple challenges such as (1) Ticks are difficult to control, (2) Vaccines control tick infestations by reducing ectoparasite fitness and reproduction, (3) Vaccine efficacy against multiple tick species, (4) Impact of tick strain genetic diversity on vaccine efficacy, (5) Antigen combination to improve vaccine efficacy, (6) Vaccine formulations and delivery platforms and (7) Combination of vaccines with transgenesis and paratransgenesis. Tick vaccine antigens evolved from organ protein extracts to recombinant proteins to chimera designed by vaccinomics and quantum vaccinomics. Future directions will advance in these areas together with other novel technologies such as multiomics, AI and Big Data, mRNA vaccines, microbiota-driven probiotics and vaccines, and combination of vaccines with other interventions in collaboration with regions with high incidence of tick infestations and tick-borne diseases for a personalized medicine approach.